Penggunaan Model Examples Non Examples untuk Peningkatan Hasil Belajar IPA Pada Materi Gaya - Olivia, Nadia; Indriyani, Vivi; Munir, Misbahul (STKIP Andi Matappa Pangkep, 2024)
To make learning more interesting and improve student learning outcomes, innovation is needed in the learning process. One way that can be done is by using innovative learning models that are appropriate to the material being taught, such as the Non-Example Model in science learning. This research aims to evaluate the improvement in science learning outcomes regarding style using the example non example model in class IV students at SDN 13 Balai Kurai Taji in the 2022/2023 academic year. The research method used is Classroom Action Research by Kemmis and Mc. Taggart, implemented in two cycles. Each cycle consists of four stages: planning, implementation, action, observation, and reflection. The research subjects consisted of 18 grade IV students, with 9 male and female students each. Data is collected through observations and tests, then analyzed to reach conclusions. The results of the research showed an increase in the initial average score of 62.78 with 28% completeness, after completing cycle I it increased to an average student score of 70.28 with 56% completeness. Then in Cycle II it increased significantly to 85 with a completion rate of 89%.